IMPLEMENTASI TATA RIAS TRADISIONAL SOLO PUTRI DALAM PROGRAM MAGANG MUA BAGI MAHASISWA TATA KECANTIKAN - Savia Fitrianing Tyas; A’ida Maulina; Anisa Shinta Dewi; Taufan Ali Achmadi; Pramesti Adika Ratri; Ifa Nurhayati (STKIP Subang, 2026)
This study aims to describe the implementation of traditional Solo Putri makeup in a Makeup Artist (MUA) internship program for beauty students and to examine its contribution to improving competencies and preserving traditional culture. The study employed a qualitative method with a descriptive approach. Data collection techniques included observation, interviews, and documentation involving beauty students, internship supervisors, and MUA practitioners who applied Solo Putri makeup in fieldwork practice activities. The data were analyzed through data reduction, data presentation, and conclusion drawing stages. The results showed that the internship program provided students with direct practical experience in applying traditional Solo Putri makeup, including facial makeup techniques, paes formation, bun arrangement, and the installation of traditional accessories. The internship activities also improved students’ technical skills, work professionalism, and communication abilities in beauty service practices. In addition, the implementation of Solo Putri makeup in the internship program contributed to the preservation of local culture by introducing the philosophical values and aesthetics of traditional makeup to younger generations. However, the implementation of the internship program still faced several challenges, such as limited opportunities to practice traditional makeup and students’ lack of understanding of the cultural philosophy behind Solo Putri makeup. Based on the findings, it can be concluded that the implementation of traditional Solo Putri makeup in the MUA internship program plays an important role in improving the competencies of beauty students while also serving as a means of preserving traditional culture amid the development of modern makeup trends.